Paradigms in public policy theory and practice of paradigm shifts in the EU - Burns, Tom R.; Calvo, Dolores; Carson, Marcus; ebrary, Inc. (Frankfurt am Main ; New York : Peter Lang, 2009)
Policy action is driven, shaped and regulated by the ways in which cognitive frames and interests shape and define issues and analyses - and the involvement of particular authorities, experts, problem-definitions and solutions. To understand these processes is particularly important in the realm of democratic policymaking, where agents driven by divergent interests and alternative principles struggle to preserve or reform policy, law, and institutions. This book analyzes continuity and change in EU policy and provides a systematic understanding of the interactions between ideas, organized actors, and institutions in political, administrative and related social processes. The EU policy studies make up a rich empirical territory, ranging from food security and chemicals to energy, climate change, and gender.
PART 1. Introduction.--1. Introduction.--2. Yves Surel : The Role of Cognitive and Normative Frames in Policymaking.--PART 2. Selected Classsic Studies of Public Policy Paradigm Shifts.--3. Paradigms and Political Discourse : Protective Legislation in France and the United States before 1914 / Jane Jenson.--4. Policy Paradigms, Social Learning, and the State. The Case of Economic Policymaking in Britain / Peter A. Hall.--5. Paradigm Shifts and Policy Networks : Cumulative Change in Agriculture / William D. Coleman, Grace D. Skogstad and Michael M. Atkinson.--PART 3. EU Policy Paradigms, Thier Applications and Shifts.--6. EU Institutions and Policymaking : a Brief Overview.--7. Theoretical Framework and Methods for Conducting the EU Research on Paradigms and Paradigm Transformations.--8. Mad Cows, Pollutted Poultry and the Transfromation of EU Food Policy / Marcus Carson.--9. From Freely Traded to Product-non -grata : Banning Asbestos in the European Union / Marcus Carson.--10. The 'REACH' Saga : a revolution in Regulating Chemicals / Tom R. Burns, Dolores Calvo, Marcus Carson.--11. Emergence of an EU Energy Policy Paradigm / Svein S. Andersen.--12. Irony of the EU Climate Policy : a Crooked Path to a Paradigm Shift/ Tom R. Burns.--13. Toward a New Social Order? Mainstreaming Gender Equality in EU policymaking / Dolores Clvo, Tom R. Burns and Marcus Carson.--14. Paradigm Shift and Regime Change : Case Comparisons and Analysis .--Part 4. 15. Elaborating Public Policy Paradigm Theory.--16. Conclusions.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Political planning -- European Union countries; European Union countries -- Politics and government; Electronic books